PENGARUH BAURAN PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE PADA RETY PONSEL TALUK KUANTAN - Ike Sapitri; Lie Othman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
This study aims to determine the effect of product mix and promotion on smartphone purchasing decisions at Rety Ponsel Taluk Kuantan partially and simultaneously. This research method is quantitative research. The sampling method in this study used accidental sampling technique using a total sample of 100 respondents. The analysis method of this research uses simple and multiple linear regression analysis by going through the validity and reliability tests. The results showed that partially the product mix variable had a significant effect on purchasing decisions of 70.6%. And the promotion is stated to have a significant effect on purchasing decisions by 71.3%. Then from the results of simultaneous testing, it is known that the two independent variables, namely the product mix (X1) and promotion (X2) have a significant effect on the dependent variable purchasing decisions (Y) of 75.3%. Keywords: Product Mix; Promotion and Purchase Decision